The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.4049/jimmunol.181.6.3750
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Th1 Cells Facilitate the Entry of Th17 Cells to the Central Nervous System during Experimental Autoimmune Encephalomyelitis

Abstract: It has recently been proposed that experimental autoimmune encephalomyelitis, once considered the classical Th1 disease, is predominantly Th17 driven. In this study we show that myelin-reactive Th1 preparations devoid of contaminating IL-17+ cells are highly pathogenic. In contrast, Th17 preparations lacking IFN-γ+ cells do not cause disease. Our key observation is that only Th1 cells can access the noninflamed CNS. Once Th1 cells establish the experimental autoimmune encephalomyelitis lesion, Th17 cells appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
277
5
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(305 citation statements)
references
References 16 publications
18
277
5
5
Order By: Relevance
“…Although both Th1 and Th17 cells could contribute to EAE pathogenicity, it appears that the ratio between the two subsets of T cells determines the severity of EAE in that predominance of Th17 over Th1 cells exacerbates inflammation and infiltration into the CNS (Bettelli et al, 2007;Stromnes et al, 2008). Furthermore, it has been proposed that Th1 cells enter non-inflamed CNS tissues prior to Th17 cells and initiate inflammation and that they facilitate the entry of Th17 cells (O'Connor et al, 2008). We have observed that ACA 83-95 induced a relatively lesser proportion of Th1 cells when compared with PLP 139151 (16.40 vs. 22.27%) and this difference in the generation of Th1 cells might have contributed to the less severe nature of EAE induced with ACA 83-95.…”
Section: Discussionmentioning
confidence: 99%
“…Although both Th1 and Th17 cells could contribute to EAE pathogenicity, it appears that the ratio between the two subsets of T cells determines the severity of EAE in that predominance of Th17 over Th1 cells exacerbates inflammation and infiltration into the CNS (Bettelli et al, 2007;Stromnes et al, 2008). Furthermore, it has been proposed that Th1 cells enter non-inflamed CNS tissues prior to Th17 cells and initiate inflammation and that they facilitate the entry of Th17 cells (O'Connor et al, 2008). We have observed that ACA 83-95 induced a relatively lesser proportion of Th1 cells when compared with PLP 139151 (16.40 vs. 22.27%) and this difference in the generation of Th1 cells might have contributed to the less severe nature of EAE induced with ACA 83-95.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of two different CCR6 À/À mouse strains (those from Dong's group [25] and our own) showed that these mice develop disease with CS similar to [25] or higher than those of WT controls. O'Connor et al [26] nonetheless established that in the absence of IFN-g 1 cells, Th17 cells do not induce EAE. Using Th1 and Th17 cells and avoiding cross-contamination between the polarized cell populations, these authors show that only Th1 cells have access to the non-inflamed CNS.…”
Section: Discussionmentioning
confidence: 99%
“…In EAE Th17 cells are particularly important for the induction of the disease [48] and these cells enter the CNS after Th1 cells [51]. However the importance of Th17 cells in mouse models of autoimmune neuroinflammation is controversial [52].…”
Section: Tlrs In Multiple Sclerosismentioning
confidence: 99%